Young Citizens Participation: Empirical Testing of a Conceptual Model. Issue 2 (March 2020) - Miranda, Daniel; Castillo, Juan Carlos; Sandoval-Hernandez, Andrés
A growing body of literature from different disciplines addresses concepts and measurement of citizenship. The present article seeks to contribute to this field by examining the issue of youth citizenship from a comparative international perspective and proposing a simplified conceptual model that can be operationalized. This model includes a community dimension, which refers to individual's relationship with their community associations, and a civic dimension, concerning institutional processes such as voting and/or political activism. The model was tested using multigroup confirmatory factor analysis and measurement equivalence for eighth-grade students ( n = 139.875) across 38 countries that participated in the International Civic and Citizenship Study (2009). Our results find support for the proposed conceptual model and its invariance across countries, and we discuss the implications for theory and further research.